New Evidence of the Effect of Transaction Costs on Residential Mobility - Jos van Ommeren; Michiel van Leuvensteijn (Tinbergen Institute, 2002)
Transaction costs have attracted considerably attention in the theoretical literature on residential mobility. In many European countries, these costs mainly consist of ad-valorem transaction costs. In the current paper, we demonstrate empirically for the Netherlands that the transaction costs have a strong negative effect on the owners' probability of moving. Under a range of different specifications, it appears that a one percent-point increase in the value of transaction costs - as a percentage of the value of the residence - decreases ownership to ownership residential mobility rates by eight percent. The estimates imply that ownership to ownership mobility rates would be 50 percent higher in the absence of the current six percent ad-valorem buyer transaction tax. Our estimates are consistent with the observation that ad-valorem transaction costs mainly consist of buyer transaction costs.
Keywords: 330; Wohnungswechsel; Transaktionskosten; Wohneigentum; Niederlande